Pembelajaran Tari Kreatif untuk Penciptaan Karya Tari pada Anak Berkebutuhan Khusus di Slb 3 Pgri Cluring Kabupaten Banyuwangi - Erna Nur Hidayah (Syntax Corporation, 2023)
This research aims to obtain effective learning methods for children with special needs because education is essentially the right of every child of the nation, including children with special needs. This study uses descriptive qualitative, namely with the aim of explaining and providing an overview of the events that exist in the field. By using a descriptive qualitative method, the researcher obtained the result that children with special needs need to first identify their learning methods and then enter into creative exploratory processes to increase the absorption of material provided by teaching staff for children with special needs. To get maximum results, teaching staff need to evaluate students whether they can receive the material well or not. By using these three methods the researcher found that students with special needs could absorb knowledge more quickly compared to learning methods that were more based on theory.